Uzbekistan Folk Medicine Healing Morocco ( Salvia Insignis) Plant Significance (Texas Journal of Multidisciplinary Studies, 2022)
In this article shows that growth of curative mawrak(salvia) in accordance with climate condition of termiz that they are fully adopted to local condition.